Zebrafish Model-Based Assessment of Indoxyl Sulfate-Induced Oxidative Stress and Its Impact on Renal and Cardiac Development - Paul Wei-Hua Tang; Ping-Hsun Wu; Yi-Ting Lin; Chen-Hao Chiu; Tien-Li Cheng; Wen-Hui Guan; Hugo You-Hsien Lin; Kun-Tai Lee; Yau-Hung Chen; Chien-Chih Chiu; Wangta Liu (MDPI AG, 2022)
Kidney disease patients may have concurrent chronic kidney disease-associated mineral bone disorder and hypertension. Cardiovascular disease (CVD) and neuropathy occur due to kidney failure-induced accumulation of uremic toxins in the body. Indoxyl sulfate (IS), a product of indole metabolism in the liver, is produced from tryptophan by the intestinal flora and is ultimately excreted through the kidneys. Hemodialysis helps renal failure patients eliminate many nephrotoxins, except for IS, which leads to a poor prognosis. Although the impacts of IS on cardiac and renal development have been well documented using mouse and rat models, other model organisms, such as zebrafish, have rarely been studied. The zebrafish genome shares at least 70% similarity with the human genome; therefore, zebrafish are ideal model organisms for studying vertebrate development, including renal development. In this study, we aimed to investigate the impact of IS on the development of zebrafish embryos, especially cardiac and renal development. At 24 h postfertilization (hpf), zebrafish were exposed to IS at concentrations ranging from 2.5 to 10 mM. IS reduced survival and the hatching rate, caused cardiac edema, increased mortality, and shortened the body length of zebrafish embryos. In addition, IS decreased heart rates and renal function. IS affected zebrafish development via the ROS and MAPK pathways, which subsequently led to inflammation in the embryos. The results suggest that IS interferes with cardiac and renal development in zebrafish embryos, providing new evidence about the toxicity of IS to aquatic organisms and new insights for the assessment of human health risks. Accordingly, we suggest that zebrafish studies can ideally complement mouse model studies to allow the simultaneous and comprehensive investigation of the physiological impacts of uremic endotheliotoxins, such as IS, on cardiac and renal development.